Financial Integration between Iran, OPEC and the Shanghai Organization - Saghar Nikpour; Mojtaba bahmani; sayyed Abdolmajid Jalaee; Mehdi Nejati (Iranian Journal of Finance, 1999)
This article investigates the financial convergence between Iran, OPEC & the Shanghai Organization trade groups, of which Iran is a member.  The analysis covers the period of 2005 to 2017.In order to examine the convergence dynamics of these financial markets; we have employed the Philips and Sul (2007) methodology, which uses a nonlinear time-varying factor model. This paper provides a comprehensive picture of the financial systems within Iran and its convergence clubs by testing the convergence of their money market with domestic credit to private sector by banks (% of GDP), deposit and lending interest rate, real interest rate, and capital market with Stocks traded, total value (% of GDP). The empirical findings show that money and stock markets of OPEC and the Shanghai group do not form a homogenous convergence club. Results show that Iran has convergence with some countries in OPEC and the Shanghai group in money and stock markets, which can be explained by their similar economic indicators in both markets. Furthermore, the convergence speed between Iran and the Shanghai countries is higher than that of Iran and OPEC countries, which proves that joint trade agreements are stronger reasons for convergence than the oil factor. Iran should implement further structural reforms in order to achieve greater financial convergence with its joined groups.